Radiomics Based on CECT in Differentiating Kimura Disease From Lymph Node Metastases in Head and Neck: A Non-Invasive and Reliable Method - Zhang, Ying; Yu, Shujing; Zhang, Li; Kang, Liqing (Frontiers in Oncology, 2020)
A retrospective analysis of 14 patients of head and neck Kimura disease (a total of 38 enlarged lymph nodes) and 39 patients with head and neck lymph node metastases (a total of 39 enlarged lymph nodes) confirmed by biopsy or surgery resection was conducted. All patients accepted CECT within ten days before biopsy or surgery resection. Radiomic features based on venous phase CECT were generated automatically from Artificial-Intelligence Kit (AK) software. All lymph nodes were randomly divided into the training set (n= 54) and testing set (n= 23) in a ratio of 7:3. ANOVA+ Mann-Whiney, Spearman Correlation, least absolute shrinkage and selection operator (Lasso) and Gradient Descent (GBDT) were introduced for the reduction of the highly redundant features. Binary Logistic Regression (BLR) model was constructed based on the selected features. ROC was used to evaluate the diagnostic performance of the features and model. Finally, a nomogram was established for model application. Results: Seven features were screened out at the end, significant difference was found between the two groups for all the features with area under the curves (AUCs) ranged from 0.759 to 0.915. The AUC of the model's identification performance was 0.970 in the training group and 0.977 in the testing group. The disease discrimination efficiency of the model was better than that of any single feature. Conclusions: The radiomic features and the model based on these features on venous phase CECT images had very good performance for the discrimination between Kimura disease and lymph node metastases in the head and neck.